Prospecting technologies for aquaculture in virtual fairs (Research, Society and Development, 2022)
This study aims to explore the technological innovations presented in aquaculture virtual fairs and to identify the segments that stand out the most to subsidize the captive production of shrimp and fish. The prospective study was developed from the information compilation collected at Aqua Expo El Oro Online and International Fish Congress Brasil Digital, both fairs held in 2020. Among the results obtained, segments were identified that offered products with high know-how directed to new crop trends. The animal nutrition and health segment stood out, with a wide supply of inputs, as well as technologies aimed at automated feeding in nurseries, demonstrating the nutritional importance for coping with diseases in aquaculture production. In addition, the events featured lectures with leading aquaculture professionals who reported on the impacts of the Covid-19 pandemic on international trade for the sector.